PENGARUH UNSPRUNG MASS PADA SEPEDA MOTOR DENGAN SISTEM TRANSMISI CONTINUOUS VARIABLE TRANSMISSION (CVT) - Handayanto, Rahmadya Trias (RESULTAN : Jurnal Kajian Teknologi, 2010)
For many years, engineers have been using programming language for calculating their designs. That languages are Fortran, C++, Basic and other console program and also Visual Basic, Visual C++, Delphi, Java and other GUI based program. After they have finished, sometimes they found inappropriate result, so they must recalculate again. We could not only say that our design was right or wrong, designer must know what is the best result from our calculation based on nice, comfort, smooth and safety In this paper I try to choose which programming language that support both numerical computation and simulation at the same time. With MATLABI try to show the simple coil spring design of two derees of freedom of suspension system and at the same time simulate the result by step response, impulse response, root locus and bode diagram. With this simple script we can compare CVT transmission with manual transmission in motorcycle related to unsprung mass effect